Pragmatic Relations in the Communication of Public Groups in the Russian Social Network Vkontakte. (3rd July 2019) - Liebschner, Andrea
ABSTRACT: This research project deals with the analysis and classification of pragmatic relations with act-types in messages on the public message wall of three selected public groups in the Russian social network Vkontakte. The theories of Sinclair and Coulthard (1975), Korpimies (1978), Diekmannshenke (1999) and Tuor (2009) on exchange structures and act types served as a starting point for the development of a new classification of act types typical for communication on Vkontakte . The practical analysis revealed and classified 29 different act types which support the pragmatic relations between individual messages on the public message wall of Vkontakte . The analysis showed that a large group of acts in Vkontakte messages consists of multimedia-files such as audio-files, video-files, hyperlinks, which can support the pragmatic connection between messages. These files can form the single content of messages or interact with the verbal text in the messages.